Populism and Collective Memory - Manucci, Luca (2022)
Populism is a widespread political phenomenon present in countries across the globe. To explain the success of populist actors and discourses, I claim it is essential to consider the long-term impact of authoritarian legacies on national political culture, individual attitudes, and electoral behavior. In the first section, I discuss the importance of collective memories in molding identities and structures of power. I then present the relevant literature on democratization and authoritarian legacies, explaining how to integrate these strands of literature with the study of populism. In the following section, I examine cases from Europe and Latin America that are suitable to study the populist present through the lenses of collective memories of authoritarian regimes. In the conclusions, I discuss possible directions for future research and suggest that other types of memories, including collective memories about colonialism and civil wars, can have a relevant impact on populism.